Pengenalan dan Pelatihan Tentang Ilmu Mawaris - Valentina Monoarfa; Moh Dwi Cahyo Paputungan; Rahmat Rizaldi Paputungan; Silvia Goiyo; Yolanda Dwi Cahyani Niode (Komunal Jurnal Pengabdian Masyarakat, 2022)
In general, Muslims regarding the distribution of inheritance and calculation procedures lack understanding and the difficulty of also getting experts in the field of inheritance distribution according to Islamic law (faraidh), this is an issue for the Muslim community, especially for heirs who want to divide inheritance according to law Islam. The author uses backward chaining methods in designing expert systems. The result of this research is the design of an expert system for dividing inheritance that can be used by the general public to help Islam solve the problem of calculation & inheritance.